IUS CONTITUENDUM PENEGAKAN HUKUM POLITIK UANG PEMILIHAN KEPALA DAERAH DI INDONESIA (Jurnal Bawaslu Provinsi Kepulauan Riau, 2020)
Money politics in general elections and regional head elections continues to be an interesting problem to be discussed but has the power of resolution which can be said to be weak. As we know that law will run well when three main factors work well, namely the substance of the law, legal structure and legal culture. If viewed based on the substance of the law, money politicsregulation in the election law has accommodated the legal needs. However, there are important things that should be noted together, which are related to the elements of TSM that must be fulfilled so that it can be said as money politics with disqualification sanctions. In addition, the legal culture as an element of the legal system is of particular concern in the enforcement of money politics in this paper. No matter how good the regulations and how many law enforcement agencies elect the regional head, if not accompanied by a good legal culture, then the law enforcement will only be in vain.
Keywords: money politics; ius contituendum; law enforcement